Constructing the criollo archive : subjects of knowledge in the Bibliotheca mexicana and the Rusticatio mexicana - Higgins, Antony, 1964- (Purdue studies in Romance literatures, 2000)
"In Constructing the "Criollo" Archive, Antony Higgins brings to light the dynamic of knowledge and power that unfolds in the writings of the criollos of eighteenth-century New Spain and Guatemala